Informing emergency care for COVID‐19 patients: The COVID‐19 Emergency Department Quality Improvement Project protocol. (21st April 2020) - O'Reilly, Gerard M; Mitchell, Rob D; Noonan, Michael P; Hiller, Ryan; Mitra, Biswadev; Brichko, Lisa; Luckhoff, Carl; Paton, Andrew; Smit, De Villiers; Santamaria, Mark J; Cameron, Peter A
Abstract: Objectives: There is an urgency to support Australian ED clinicians with real‐time tools as the COVID‐19 pandemic evolves. The COVID‐19 Emergency Department (COVED) Quality Improvement Project has commenced and will provide flexible and responsive clinical tools to determine the predictors of key ED‐relevant clinical outcomes. Methods: The COVED Project includes all adult patients presenting to a participating ED and meeting contemporary testing criteria for COVID‐19. The dataset has been embedded in the electronic medical record and the COVED Registry has been developed. Results: Outcomes measured include being COVID‐19 positive and requiring intensive respiratory support. Regression methodology will be used to generate clinical prediction tools. Conclusion: This project will support EDs during this pandemic.